Role of a pre-operative radiological scoring system in determining resectability for potentially resectable hilar cholangiocarcinoma. Issue 2 (February 2019) - Bird, Nicholas; McKenna, Adrian; Dunne, Declan; Francis, Ben; Fenwick, Stephen; Poston, Graeme; Jones, Robert; Malik, Hassan
Abstract: Aims: Cholangiocarcinoma is a rare cancer arising from the biliary tree. Case series indicate that 25–40% of all borderline resectable primary tumours are potentially resectable. The Memorial Sloane Kettering System (MSKCC) stratifies patients for resectability by longitudinal and radial extension of the hilar tumour. The Bismuth-Corlette system describes the longitudinal extension of the tumour within the biliary duct system. We sought to validate and, if possible, augment these two scores within an independent validation cohort. Methods: Patients diagnosed with hilar cholangiocarcinoma between January 2009 and December 2016 were analysed from a prospectively held database. Patients with distal cholangiocarcinoma, peripheral cholangiocarcinoma and gallbladder cancer were excluded. Comparison of surgical findings to pre-operative radiological imaging was undertaken at the time of surgery. Results: The validation cohort was formed of 198 patients, of which, 55 (27.8%) patients underwent resection. Logistic regression analyses identified that BC score, MSKCC score, age at diagnosis and left artery involvement were all significant independent predictor's univariately. BC score explained 28% of the variability in resectability compared to 26% explained by MSKCC. In combination, the model consisting of BC score, age at diagnosis and left artery involvement explained 39% of variability in resectability compared to the 34% explained same model including MSKCC score instead of BC score. Conclusion: In this cohort an augmented BC score, incorporating left hepatic artery involvement, is more discriminative in predicting resectability than the current MSKCC system.